2016
DOI: 10.19044/esj.2016.v12n4p68
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Human Capital on Competitive Performance: An Empirical Study on Jordanian Pharmaceutical Companies

Abstract: The study is aimed at knowing the impact of human capital on competitive performance in Jordanian pharmaceutical companies. The study sample consisted of Jordanian human medicines manufacturing companies listed in the Jordanian Association of Pharmaceutical Manufacturers’ records of manufacturing companies for 2015. This amounted to 15 companies. The sampling unit and the analysis included individuals working in these companies from managers to department heads at various administrative levels. To achieve its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…However, Anghel et al (2018) pointed out that an increase in R&D expenditure results in an increase in ROA and ROE in pharmaceutical industry. Almasarweh et al (2019) found significant association between marketing performance and three dimensions of IC (HC, SC, and technological capital) in Jordanian pharmaceutical sector. Basuki and Kusumawardhani (2012) found that IC components (i.e.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…However, Anghel et al (2018) pointed out that an increase in R&D expenditure results in an increase in ROA and ROE in pharmaceutical industry. Almasarweh et al (2019) found significant association between marketing performance and three dimensions of IC (HC, SC, and technological capital) in Jordanian pharmaceutical sector. Basuki and Kusumawardhani (2012) found that IC components (i.e.…”
Section: Discussionmentioning
confidence: 83%
“…This industry generally has a long return period from R&D stage to final product launch, but the successful development of new drugs usually brings huge profits to investors (Huang 2014). These make it an attractive proposition for IC research (Almasarweh et al 2019;Amin and Aslam 2017;Anghel et al 2018;Basuki and Kusumawardhani 2012;Bharathi Kamath 2008;Chowdhury, Rana, and Azim 2019;Huo 2012;Lv and Han 2015;Mehralian et al 2012;Sivakoumar and Kasilingam 2014;Smriti and Das 2017;Thanikachalam, Muninarayanappa, and Prabakaran 2018;Vishnu and Kumar Gupta 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Almasarweh )2016(: The research studied the effect of human capital on competition between pharmaceutical companies in Jordan, and showed that there is a relationship between human capital and competition.…”
Section: Literature: a Brief Reviewmentioning
confidence: 99%
“…Corporate marketing is mainly affected by four factors, namely, product, price, channel, and promotion. The effectiveness of corporate marketing mix relies on the strategic choice and integrated use of the four factors, both of which greatly promote the brand building, personalization, and contextualization of corporate marketing [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%